Pentahelix Model of Cultural Transmission in Wayang On The Street Performances in Semarang’s Old Town - Dwi Yullastuti; Paramitha Dyah Fitriasari; Wiwik Sushartami (Universitas Negeri Medan, 2025)
The sustainability of traditional performing arts in the modern era requires innovative strategies to ensure cultural relevance and intergenerational transmission. This study investigates the cultural transmission process within the Wayang On The Street (WOTS) performance, held in the Old Town area of Semarang in 2024, as a collaborative model integrating traditional values into contemporary public spaces. Employing a descriptive qualitative case study, data were collected through participant observation, in-depth interviews with artists, cultural officials, and community members, and documentation of the Pandawa Pitu performance during the Semarang Old Town Festival. The analysis focuses on the interaction among actors within the pentahelix framework—academics, government, business, media, and community—in sustaining traditional performing arts in urban contexts. Findings reveal that WOTS serves not only as a platform for artistic expression but also as a medium for cultural education, public participation, and community empowerment. The synergy among stakeholders strengthens the adaptive capacity of traditional arts and fosters sustainable cultural ecosystems. This study contributes to the theoretical development of cultural transmission by emphasizing the role of multi-stakeholder collaboration as a foundation for innovative cultural preservation in contemporary society.